Persistent innate immune dysfunction and ZIKV replication in the gastrointestinal tract during SIV infection in pigtail macaques - Tisoncik-Go, Jennifer; Lewis, Thomas B.; Whitmore, Leanne S.; Voss, Kathleen; Niemeyer, Skyler; Dai, Jin; Kim, Paul; Hubbell, Kai; Iwayama, Naoto; Ahrens, Chul; Wangari, Solomon; Murnane, Robert; et al. (Frontiers in Immunology, 2025)
Mosquito-borne flaviviruses, including dengue (DENV) and Zika (ZIKV) viruses, have caused widespread epidemics in areas with high HIV prevalence, partly due to the expanded geographic range of arthropod vectors. Despite the occurrence of large flavivirus outbreaks in areas with high HIV prevalence, little is known about the effects of flavivirus infection in people living with HIV (PLWH). Here, we use a pigtail macaque model of HIV/AIDS to investigate the impact of simian immunodeficiency virus (SIV)-induced immunosuppression on ZIKV replication and pathogenesis. During acute SIV infection, peripheral ZIKV cellular targets expanded and innate immune activation increased. In vitro, peripheral blood mononuclear cells (PBMC) from SIV infected pigtail macaques were less permissive to ZIKV infection. In vivo, ZIKV viremia was delayed and ZIKV was more persistent in the gastrointestinal tissues of SIV-ZIKV co-infected animals. This persistence was associated with changes in innate cellular (monocytes, neutrophils) recruitment to the blood and tissues, reduced anti-ZIKV immunity, and sustained expression of peripheral inflammatory and innate immune genes. Collectively, these findings uniquely suggest that untreated SIV infection may promote inflammatory cellular innate responses and create a state of persistent immune activation that contributes to prolonged ZIKV viremia and persistence in the gastrointestinal tract. Furthermore, these results suggest that PLWH and other immunocompromised individuals could be at higher risk for prolonged ZIKV infection, potentially extending the window of ZIKV transmission. These insights highlight the importance of including PLWH in strategies for deploying vaccines and treatments against ZIKV.